Identification of Gate Turn-Off Thyristor Switching Patterns Using Acoustic Emission Sensors - Maciej Kozak; Artur Bejger; Arkadiusz Tomczak (Sensors, 2020)
Modern seagoing ships are often equipped with converters which utilize semiconductor power electronics devices like thyristors or power transistors. Most of them are used in driving applications such as powerful main propulsion plants, auxiliary podded drives and thrusters. When it comes to main propulsion drives the power gets seriously high, thus the need for use of medium voltage power electronics devices arises. As it turns out, power electronic parts are the most susceptible to faults or failures in the whole electric drive system. These devices require efficient cooling, so manufacturers design housings in a way that best dissipates heat from the inside of the chips to the metal housing. This results in susceptibility to damage due to the heterogeneity of combined materials and the difference in temperature expansion of elements inside the power device. Currently used methods of prediction of damage and wear of semiconductor elements are limited to measurements of electrical quantities generated by devices during operation and not quite effective in case of early-stage damage to semiconductor layers. The article presents an introduction and preliminary tests of a method utilizing an acoustic emission sensor which can be used in detecting early stage damages of the gate turn-off thyristor. Theoretical considerations and chosen experimental results of initial measurements of acoustic emission signals of the medium voltage gate turn-off thyristor are presented.